2018
DOI: 10.1088/1748-9326/aadb44
|View full text |Cite
|
Sign up to set email alerts
|

It’s not the heat, it’s the vulnerability: attribution of the 2016 spike in heat-associated deaths in Maricopa County, Arizona

Abstract: Health risk assessments for extreme heat and the design of corresponding interventions can be enhanced with more information regarding causal drivers of year-to-year variability in adverse outcomes. Summer 2016 was a record-setting year in terms of summer heat and its impacts on health in Maricopa County, Arizona, USA. The month of June was the warmest observed in the county and the six-month warm season spanning May through October was the fourth warmest. In the same year, a record number of heat-associated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Heat stress occurs when households are unable to afford or access energy to cool their homes. The health effects from this type of energy insecurity, such as increased morbidity and mortality rates, are most often seen during heatwaves when excess heat from outside conditions creates heat stress (135,141,142). Cardiovascular issues such as heat strokes, hypertension, and heart attack, dehydration, hyperthermia, and nervous system morbidities are examples of health impacts that occur under heat stress (69,135,143).…”
Section: Heat Stress and Forbearancementioning
confidence: 99%
See 2 more Smart Citations
“…Heat stress occurs when households are unable to afford or access energy to cool their homes. The health effects from this type of energy insecurity, such as increased morbidity and mortality rates, are most often seen during heatwaves when excess heat from outside conditions creates heat stress (135,141,142). Cardiovascular issues such as heat strokes, hypertension, and heart attack, dehydration, hyperthermia, and nervous system morbidities are examples of health impacts that occur under heat stress (69,135,143).…”
Section: Heat Stress and Forbearancementioning
confidence: 99%
“…Other health effects include a higher likelihood of acute renal failure (42) and increased sleep disturbances as a result of the extreme heat in inadequately cooled homes, which can exacerbate mental health conditions triggered by the stress of energy insecurity (53,57). This increase in morbidity and mortality is motivated by other social determinants of health that predict energy insecurity (142).…”
Section: Heat Stress and Forbearancementioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, some scholars use morbidity and mortality data to build multiple models between temperature and heat-associated deaths to assess the population health vulnerability risk caused by extreme heat [10][11][12][13]. Some studies found that extreme heat is only a trigger, the differences in demographic characteristics are a direct factor in mortality [14]. Therefore, the assessment results of these studies mainly reflect the risk differences of different social groups.…”
mentioning
confidence: 99%
“…Regional studies have demonstrated associations between heatassociated mortality and contextual factors, such as weather and temperature, neighborhood socioeconomic status, social isolation, and land cover. [8][9][10][11] MCDPH's heat-associated death surveillance system provides a valuable complement to these place-based analyses with detailed data on the demographic characteristics of decedents and circumstances of death. We describe findings of the Maricopa County heatassociated death surveillance system in the 11-year period (2006-2016) since its implementation to understand the circumstances of heat-associated deaths and compare these results with the findings of studies and projects that occurred during the same period.…”
mentioning
confidence: 99%